Barriers to single property model in Colombian shopping center industry - Gil, Andrés Felipe (2016)
This work explores the likely facts and characteristics that made Colombia a country, unlike the rest of the world´s main markets, in which horizontal property is still the main model by which shopping centers are developed. Starting by pointing out the implications of this model, this work uses theory and empirical research available that, in contrast, support the idea that single property model, in the other hand, leads towards a developer-retailer arrangement that aligns their interests, maximizing rents and sales in the process. This work compares the horizontal property model with single property, under the light of available single property´s theory, in order to determine whether their results could be similar or comparable. Three concepts support the previous statement: i). Complementary and comparison shopping that leads to agglomeration and clustering retail; ii) Inter-store externalities allow shopping center´s developer to manage the tenant mix in order to maximize rents and sales; iii) Inter-store externalities are possible thanks to the relative draw power generated by retailers. Using exploratory research, this work analyses the main factors that restrained Colombia to develop single property shopping centers after 40 years of industry history. This paper relies on in-depth interviews from industry experts to gather those factors that prevents Colombian industry to consolidate the single property model. International Isolation, which prevents Colombia to be foreign direct investment recipient until mid 2000´s|, house-building rationality exported to shopping center development and retailers investing in real estate, are the main factors.